Whole-Exome Sequencing of Matched Primary and Metastatic Papillary Thyroid Cancer - Masoodi, Tariq (Thyroid, 2020)
Background: Distant metastasis is a rare occurrence in thyroid cancer, and it can be associated with poor prognosis. The genomic repertoires of various solid malignancies have previously been reported but remain underexplored in metastatic papillary thyroid cancer (PTC). Furthermore, whether distant metastases harbor distinct genetic alterations beyond those observed in primary tumors is unknown. Methods: We performed whole-exome sequencing on 14 matched distant metastases, primary PTC tumors, and normal tissues. Point mutations, copy number alterations, cancer cell fractions, and mutational signatures were defined using the state-of-the-art bioinformatics methods. All likely deleterious variants were validated by orthogonal methods. Results: Genomic differences were observed between primary and distant metastatic deposits, with a median of 62% (range 21–92%) of somatic mutations detected in metastatic tissues, but absent from the corresponding primary tumor sample. Mutations in known driver genes including BRAF, NRAS, and HRAS were shared and preferentially clonal in both sites. However, likely deleterious variants affecting DNA methylation and transcriptional repression signaling genes including SIN3A, RBBP1, and CHD4 were found to be restricted in the metastatic lesions. Moreover, a mutational signature shift was observed between the mutations that are specific or enriched in the metastatic and primary lesions. Conclusions: Primary PTC and distant metastases differ in their range of somatic alterations. Genomic analysis of distant metastases provides an opportunity to identify potentially clinically informative alterations not detected in primary tumors, which might influence decisions for personalized therapy in PTC patients with distant metastasis.